Optimasi Kinerja Motor Sebagai Penggerak Belt Conveyor Berbasis Modified Firefly Algorithms - Puji Astoro, Fany Wahyu; Ali, Machrus; Ajiatmo, Dwi (FORTEI Regional VII Jawa Timur, 2025)
Abstract - Modern manufacturing industries require reliable and efficient drive systems, including three-phase induction motors in belt conveyors that ensure continuous material distribution. This study investigates the performance of a 1.5 kW three-phase induction motor at PT. Dayasa Aria Prima, which faces high-load conditions and frequent trips on the Thermal Overload Relay (TOR) due to significant current surges when loads exceed 80% capacity, leading to stator overheating and operational shutdown. A quantitative-experimental approach was applied by measuring current and voltage under varying loads to determine safe operating limits and optimal protection settings. A conveyor system model was developed using electrical engineering parameters, and a PID controller was optimized with a Modified Firefly Algorithm (MFA) in MATLAB. The MFA was enhanced with dynamic adaptation and additional exploitation operators to improve convergence speed and robustness against local optima. Results indicate a safe operating load range of 1.3–1.4 kW, with the MFA-optimized PID controller stabilizing conveyor speed, increasing control efficiency by 11.6%, and reducing overload risk by 42% compared to conventional control. The novelty lies in the application of MFA using real industrial field data, the integration of experimental measurements with numerical simulations for precision improvement, and the enhancement of MFA for faster convergence and better stability. This research offers practical value for industries dependent on belt conveyors by providing an adaptive, energy-efficient motor control strategy that minimizes downtime, extends motor lifespan, and reduces operational costs.